FELTARBEJDE OM ETNISK IDENTITET: Et canadisk indiansk samfund i 1990’eme - Braroe, Niels Winther (Tidsskriftet Antropologi, 1997)
Niels Winther Braroe: Fieldwork on Ethnic Identity: A Canadian Indian Community in the 1990’s This article describes some obstacles to fieldwork in a Plains Cree Indian com-munity. The research is a continuation of study begun in the 1960’s, after an absence of twenty-five years. Two areas of “trouble” are discussed. The first has to do with the effects of a book about the community published by the author; the second set of difficulties results from newly emergent factional divisions on the reserve. Both of these are relevant to the author’s interest in changing expressions of ethnic identity of the band, and political and economic changes associated with a new Indian cultural self-image. The author describes some approaches taken to negotiate these obstacles.